2005
DOI: 10.1159/000084324
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Macrolide Antibacterial Drug, Tylosin, on TNBS-Induced Colitis in the Rat

Abstract: Bacterial antigens, such as intestinal microflora, are known to play a role in the pathogenesis of human inflammatory bowel disease (IBD). Tylosin, a macrolide antimicrobial agent, has proven to be effective in cat and dog chronic colitis, but the reasons underlying this efficacy are still unclear. In the present study we evaluated the effects of tylosin on 2,4,6-trinitrobenzenesulfonic acid (TNBS)-induced colitis in the rat, in comparison with the antibacterial drug metronidazole and the corticosteroid budeso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 75 publications
1
9
0
Order By: Relevance
“…However, at 1,000 mg/kg, AL-Na significantly ameliorated DSS-induced colitis in these mice. Moreover, 500 mg/kg AL-Na inhibited the progression of TNBS-induced colitis, as indicated by decreased MPO and serum amyloid A, which are produced in proportion to the severity of the colitis [27,28,29,30]. Therefore, it is proposed that oral AL-Na promotes mucosal healing after colonic inflammation in experimental colitis in mice.…”
Section: Discussionmentioning
confidence: 99%
“…However, at 1,000 mg/kg, AL-Na significantly ameliorated DSS-induced colitis in these mice. Moreover, 500 mg/kg AL-Na inhibited the progression of TNBS-induced colitis, as indicated by decreased MPO and serum amyloid A, which are produced in proportion to the severity of the colitis [27,28,29,30]. Therefore, it is proposed that oral AL-Na promotes mucosal healing after colonic inflammation in experimental colitis in mice.…”
Section: Discussionmentioning
confidence: 99%
“…[193][194][195][196][197] Animal studies supported these observations, where pretreatment of mice with antibiotics showed significant alleviation of subsequent intestinal inflammation in several models. [198][199][200][201] In addition, knockout mice raised in conventional conditions developed spontaneous chronic colitis, while the mice did not develop intestinal inflammation if raised in germ-free conditions. 202 Recent studies have illustrated that Faecalibacterium prausnitzii, a prominent intestinal microorganism, was reduced in some patients with CD.…”
Section: Altered Mucosal Microbesmentioning
confidence: 99%
“…However, this hypothesis has not been substantiated . Other hypotheses about tylosin's mode of action include promotion of beneficial commensal bacteria, decrease in total bacterial load in the small intestine, and suppression of aberrant mucosal immune responses …”
Section: Introductionmentioning
confidence: 99%